On-line monitoring of multi-component strain development in a tufting needle using optical fibre Bragg grating sensors - Chehura, Edmon; Dell'Anno, Giuseppe; Huet, Tristan; Staines, Stephen E.; James, Stephen W.; Partridge, Ivana K.; Tatam, Ralph P. (Institute of Physics (IOP), 2014)
Dynamic loadings induced on a tufting needle during the tufting of dry carbon fibre preform via a commercial robot-controlled tufting head were investigated in situ and in real-time using optical fibre Bragg grating (FBG) sensors bonded to the needle shaft. The sensors were configured such that the axial strain and bending moments experienced by the needle could be measured. A study of the influence of thread and thread type on the strain imparted to the needle revealed axial strain profiles which had equivalent trends but different magnitudes. The mean of the maximum axial compression strains measured during the tufting of a 4-ply quasi-isotropic carbon fibre dry preform were - 499 ± 79 με, - 463 ± 51 με and - 431 ± 59 με for a needle without thread, with metal wire and with Kevlar® thread, respectively. The needle similarly exhibited bending moments of different magnitude when the different needle feeding configurations were used.